Gothic Matters of De-Composition: The Pastoral Dead in Contemporary American Fiction - Armstrong, John (Text Matters: A Journal of Literature, Theory and Culture, 2016)
In Alice Walker’s vignette “The Flowers,” a young black girl’s walk in the woods is interrupted when she treads “smack” into the skull of a lynched man. As her name predicates, Myop’s age and innocence obstruct her from seeing deeply into the full implications of the scene, while the more worldly reader is jarred and confronted with a whole history of racial violence and slavery. The skeleton, its teeth cracked and broken, is a temporal irruption, a Gothic “smack” that shatters the transience of the pastoral scene with the intrusion of a deeper past from which dead matter/material de-composes (disturbs, unsettles, undoes) the story’s present with the violent matter/issue of racism. Walker’s story is representative of an important trope in fiction, where the pastoral dead speak through the details of their remains, and the temporal fabric of text is disrupted by the very substance of death. Against the backdrops of Terry Gifford’s post-pastoral and Fred Botting’s Gothic understanding of the literary corpse as “negative[ly] sublime,” this essay explores the fictional dead as matter unfettered by genre, consistently signifying beyond their own inanimate silences, revealing suppressed and unpalatable themes of racial and sexual violence, child abuse and cannibalistic consumerism. Along with Walker’s story, this study considers these ideas through new readings of Stephen King’s novella The Body, Raymond Carver’s story “So Much Water So Close to Home,” and The Road by Cormac McCarthy. While these writers may form an unlikely grouping in terms of style, each uses pastoral remains as significant material, deploying the dead as Gothic entities that force the reader to confront America’s darkest social and historical matters.